Towards a Managed Extensible Control Plane for Knowledge-Based Networking - O'Sullivan, Declan; Lewis, David (Springer, 2006)
This paper proposes an open, extensible control plane for a global event service, based on semantically rich messages. This is based on the novel application of control plane separation and semantic-based matching to Content-Based Networks. Here we evaluate the performance issues involved in attempting to perform ontology-based reasoning for content-based routing. This provides us with the motivation to explore peer-clustering techniques to achieve efficient aggregation of semantic queries. The clustering of super-peers using decentralized policy engineering will deliver the incremental deployment of new peer-clustering strategies.
17th IFIP/IEEE International Workshop on Distributed Systems: Operations and Management (DSOM 2006)
PUBLISHED
Dublin, Ireland
Keywords: Computer Science; Digital Engagement; Telecommunications